Kiamat Amat Dahsyat / Umar Sulaiman Abdullah Al -Asyqon ; penerjemah , Rusdianto ; penyunting Kuswaidi Syafiie - Al - Asyqar, Umar Sulaiman Abdullah; Rusdianto Syafi'ie, Kuswaidi (2010)
XI, 517 hlm 21 cm